THE RENAISSANCE KING: ZAIN-UL-ABIDIN’S REIGN IN KASHMIR - Shabir Ahmad Lone; R. Abida Begum; S. Nazeemunnisa Begum; Javad Ahmad Mir; Mohammad Ishaq Lone (CV. RADJA PUBLIKA, 2025)
Sultan Zain-ul-Abidin, popularly known as Budshah (The Great King), was a transformative ruler whose reign (1420–1470 A.D.) marked a golden era in Kashmiri history. Revered for his visionary leadership, he championed religious tolerance, cultural revival, and economic prosperity, earning him the title of